THE IMPACT OF WORKLOAD AND PERCEIVED ORGANIZATIONAL SUPPORT ON NURSING PERFORMANCE IN SAUDI ARABIAN HOSPITALS - Maryam Saad Khalif Al-Rashidi, Entisar Trad Ghazi Al-Dhafiri, Kholoud Obaid Al-Shammari, Eazizah Talal Al-Shammari, Bidawr Khaled Al-Mutairi, Fayza Obaid Al-Shammari (Chelonian Research Foundation, 2022)
Objective: This study aimed to investigate the impact of workload and perceived organizational support on nursing performance in Saudi Arabian hospitals. Methods: A cross-sectional survey was conducted among 500 nurses working in various hospitals across different regions in Saudi Arabia. Participants completed a self-administered questionnaire assessing workload (Quantitative Workload Inventory), perceived organizational support (Survey of Perceived Organizational Support), and nursing performance (Individual Work Performance Questionnaire). Multiple linear regression analysis was used to examine the predictors of nursing performance. Results: The response rate was 94% (n=470). The mean age of participants was 32.6 years (SD=6.8), and 76% were female. Workload (β=-0.28, p<0.001) and perceived organizational support (β=0.35, p<0.001) were significant predictors of nursing performance, after controlling for demographic and work characteristics. Nurses with higher workload and lower perceived organizational support reported poorer nursing performance. Conclusion: Workload and perceived organizational support significantly influenced nursing performance in Saudi Arabian hospitals. Hospitals should implement strategies to optimize nursing workload and enhance organizational support to improve nursing performance and patient outcomes. Keywords: workload, perceived organizational support, nursing performance, Saudi Arabia